In-situ fabrication of novel flower like MoS2/CoTiO3 nanorod heterostructures for the recyclable degradation of ciprofloxacin and bisphenol A under sunlight. (October 2021) - Dadigala, Ramakrishna; Bandi, Rajkumar; Alle, Madhusudhan; Gangapuram, Bhagavanth Reddy; Guttena, Veerabhadram; Kim, Jin-Chul
Abstract: Effectual degradation of toxic water contaminants is a crucial step in water purification and designing an efficient semiconductor based hybrid structure photocatalyst is a good approach to achieve this. Benefiting from the combination of semiconductors, a series of novel visible-light active flower-like MoS2 /CoTiO3 nanorod heterostructures with excellent morphological contact interface were prepared through a facile in-situ hydrothermal process. These heterostructures were well characterized and demonstrated high photocatalytic performance for ciprofloxacin (CIP) and bisphenol A (BPA) under sunlight irradiation. Compared to pristine CoTiO3 and MoS2, the optimal catalyst (5 wt% MoS2 /CoTiO3 ) presented 39.97 and 22.32 times higher activity for CIP degradation and 26.85 and 15.66 times higher activity for BPA degradation, respectively. This improved activity can be accounted for the effective interfacial contact which promotes the efficient charge carriers separation and reduce its recombination. The catalyst exhibited decent stability and was potentially reused for five cycles without significant loss in activity. Furthermore, based on active species scavenging experiments the plausible photodegradation mechanism is discussed in detail. Graphical abstract: Image 1 Highlights: In-situ hydrothermal synthesis of flower-like MoS2 /CoTiO3 nanorod heterostructures. Efficient photocatalytic degradation of Ciprofloxacin and Bisphenol A. Efficient separation of photoexcited electron-hole pairs at MoS2 /CoTiO3 interface. Holes and hydroxyl radicals were the active species involved. Possible photodegradation mechanism was proposed.